Cascaded Acoustic Wave Sensors Based on Erbium-Doped Fiber Laser Dynamics for Intrusion Zone Identification - Woon, Sin Ling; Kwan, Kar Meng; Chong, Wu Yi; Lin, Horng Sheng; Pua, Chang Hong (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Optical based acoustic wave sensors have been implemented recently for intrusion detection. These sensors commonly involve the use of an optical time-domain reflectometer to pinpoint location, which is costly and slow. This paper reports on an acoustic sensor based on laser transient of an erbium-doped fiber laser (EDFL) which offers almost instantaneous response to external perturbations. The proposed sensor is cost-effective, simple with fast response time and is able to detect high frequency vibrations. In addition, the inherent high sensitivity of the sensor enables it to sense airborne acoustic wave. Zone identification capability was demonstrated using a sensor setup with two EDFLs. The time delay due to the relative positions of the two fibers allows the user to identify the position of the impact. The sensing length can be easily increased for long range zone identification with length up to 25 km.